Pendampingan Meningkatkan Minat Literasi Sastra Puisi Siswa Melalui Program Klub Literasi Sekolah - Hariyanto Supriyadi; Eli Rustinar; Elyusra Elyusra; Sakroni Sakroni; Man Hakim (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This Community Service Program aims to provide training and guidance in the field of literary writing for students. This activity is an effort to develop students' critical literacy skills, especially through writing skills. In addition, this activity is also a way to bring schools and students closer to literary works. The implementation method, Community Service is carried out by providing ongoing training and mentoring. The training was conducted for three days for students/participants. This training is carried out in two ways, namely inclass and outclass. Inclass training is carried out to provide a common understanding of writing literary works to students/participants, while outclass training is conducted to hone sensitivity, critical power, and intuition of students/participants to catch any existing problems. around them to be used as material in writing literary works. Based on the results of the implementation, the understanding of literary works is better than before. Likewise, students' writing skills are increasing and getting better, this is evidenced by the results of their literary works in the form of poetry anthologies. The poems they make vary, both in terms of typography, theme, and content. The students were enthusiastic and enthusiastic in participating in these activities. With the activities of fostering literary writing in schools, it can help students and the school better recognize literary literacy, especially in the field of literary writing. On the other hand, fostering literary writing in schools can help teachers form the School Literacy Movement in their respective schools, considering that there are still very few people in the school environment, so there is a need for similar activities with the aim of increasing students' competence and love for reading and writing.